Hypotypose littéraire et incrustation bédéique : essai de stylistique comparée - Bessières, Vivien (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2018)
As a dynamic picture, the literary figure of hypotyposis seems consistent with the very definition of comics, series of drawings producing motion. However, if hypotyposis is always simultaneously descriptive and narrative, comics are on the contrary sets of descriptions which sequencing produces narration. In fact, a particular device of the ninth art matches more with the literary figure: the insert, that is the inlay of one or more panels within another. Automatically, the inserting panel becomes the background, the setting of a story developed in the foreground by the inserted panels. This device is not classical. It is to be found among the pioneers or the modern and contemporary authors, who use it, like hypotyposis, for epic purposes, or to give more life to a historical re-enactment, to confront collective with individual memory, or also to make several spaces flourish in the same time and several times flourish in the same place.